Seditious Spaces - Nurul Azreen Azlan (A+BE: Architecture and the Built Environment)
The title ‘Seditious Spaces’ is derived from one aspect of Britain’s colonial legacy in Malaysia (formerly Malaya): the Sedition Act 1948. While colonial rule may seem like it was a long time ago, Malaysia has only been independent for sixty-one years, after 446 years of colonial rule. The things that we take for granted today, such as democracy and all the rights it implies, are some of the more ironic legacies of colonialism that some societies, such as Malaysia, have had to figure out after centuries of subjugation. While not suggesting that post-colonial regimes should not be held accountable for their actions, it is ironic to see a BBC commentator grilling the leader of a Commonwealth state about repressive laws and regulations inherited from the colonial era. (Even the term ‘Commonwealth’ is itself ironic, implying shared wealth, in reality it commonly meant a colonised country was contributing to the wealth of the metropolitan centre).